2014
DOI: 10.1002/ldr.2299
|View full text |Cite
|
Sign up to set email alerts
|

Profile Distribution of Carbon Fractions Under Long‐term Rice‐wheat and Maize‐wheat Production in Alfisols and Inceptisols of Northwest India

Abstract: The knowledge of profile distribution of soil organic carbon (SOC) in long-term agricultural systems could help to store atmospheric carbon in the soil. We investigated profile distribution of easily oxidisable Walkley-Black SOC pool (SOC WB ) under long-term ricewheat (R-W) and maize-wheat (M-W) cropping systems under soils of different pedogenesis. The soil samples were collected from the characteristic genetic horizons and analysed for carbon fractions. The SOC WB was the highest in soils under R-W systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Therefore, most cultivation techniques aim to optimize the soil organic matter through (zero-)tillage techniques (Costa et al, 2015;Singh et al, 2015), planting of native tree species (Tesfaye et al, 2014), mulching (Mwango et al, 2014), and land use systems (Araya et al, 2010). These activities are not observed in our database but influence the soil organic matter levels at surface and deeper horizons; moreover, the magnitude of variation is also shaped by specific pedogenic processes (Kukal et al, 2014). Hence, with the choice of our approach to test the stability of the relationship between land degradation and crop yield under an increasing level of detail, we hope to have controlled sufficiently for these confounding variables that otherwise might bias the estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, most cultivation techniques aim to optimize the soil organic matter through (zero-)tillage techniques (Costa et al, 2015;Singh et al, 2015), planting of native tree species (Tesfaye et al, 2014), mulching (Mwango et al, 2014), and land use systems (Araya et al, 2010). These activities are not observed in our database but influence the soil organic matter levels at surface and deeper horizons; moreover, the magnitude of variation is also shaped by specific pedogenic processes (Kukal et al, 2014). Hence, with the choice of our approach to test the stability of the relationship between land degradation and crop yield under an increasing level of detail, we hope to have controlled sufficiently for these confounding variables that otherwise might bias the estimation.…”
Section: Resultsmentioning
confidence: 99%
“…() estimated mean SOC contents of 3·3 kg m −2 in the topsoil (0–20 cm) of cereal crops in Turkey, while Kukal et al . () found mean SOC stocks beneath cereal crops in India of 7·1 kg m −2 in the first 18 cm.…”
Section: Discussionmentioning
confidence: 99%
“…SOC contents for croplands (5·0 kg m À2 with an average soil depth of 54 cm in SN and 3·0 kg m À2 with an average soil depth of 62 cm in CG) are also lower compared with those found in other regions under similar climatic conditions. For instance, Evrendilek et al (2004) estimated mean SOC contents of 3·3 kg m À2 in the topsoil (0-20 cm) of cereal crops in Turkey, while Kukal et al (2014) found mean SOC stocks beneath cereal crops in India of 7·1 kg m À2 in the first 18 cm.…”
Section: The Influence Of Land Use and Land Covermentioning
confidence: 99%
“…Among the many crops cultivated worldwide according to various agricultural systems, rice is one of the most harmful because of the intense labour that is required and the modifications of the natural cycles that rice production causes (El‐Shahway et al ., ; Tran Ba et al ., ). The alteration and degradation that occur because of rice monocropping are even more important considering the environment in which such cultivation is performed: lowland areas, which play a significant role in regulating C dynamics (Ono et al ., ; Kukal et al ., ).…”
Section: Introductionmentioning
confidence: 97%